ANALISIS DALAM EKONOMI SYARIAH MENJADI LANDASAN GUNA MEMPEROLEH EKONOMI MASYARAKAT INDONESIA YANG MAKMUR - Juliani Wulandari; Fauzatul Laily Nisa (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
There is an opportunity in the Sharia economy to be able to resolve the problems that exist in Indonesia, especially in the economic sector. One of the problems is poverty that occurs in Indonesian society, reaching half of the living population. Therefore, journals are written to try to solve problems. By starting from the system that exists in Indonesia, namely the economic system. So that later we can explain how the economic concept in Sharia extends to mastery of the existing economic system in Indonesia. As the religion most recently revealed by Allah SWT, Islam has various instruments in predicting and overcoming modern problems in the global era. The Al-Quran and As-Sunnah are considered to be the origins of early law in Islam, which provide guidelines so that Islamic teachings remain relevant throughout the ages. One of the strategies adopted is the application of Islamic sharia economic principles as an effort to deal with a number of economic problems faced by Indonesian society. As stated by As-Shidiqy, Islamic economics is the result of the response of Muslim thinkers to the economic challenges that existed in their time. They integrate the Koran, Sunnah, rational considerations, and practical experience in their efforts to develop economic solutions that are in accordance with Islamic teachings.